Tourism and agrotourism potentail of Vrancea county - Romania - Antoneta Petruţa Enache; Manea Drăghici (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 8th Edition of the International Symposium, November 2017, Bucharest, 2017)
The Vrancea County region is one of the important areas of the South-East Development Region through tourism potential, through the natural cadre it possesses, the historical monuments and architecture, folk art, because here live householder people who keep the ancestral traditions, adding the quality of the offered tourism services. The tourism potential represents, truly, the primary tourism offer (potential) which, together with the existing tourism structures (accommodation structure and specific infrastructure) form the real tourism offer or the patrimonial tourism. In this essay we analyze the tourism accommodation structures and the accommodation capacity, the tourist circulation, the net usage of the operative capacity coefficient in Vrancea County.
Keywords: Q11; 330; tourism; agrotourism; circulation